AB0141 Low dose IL-2 circumvented MTOR signaling in T cells in the treatment of SLE. (15th June 2017) - He, J; Sun, X; Li, J; Zhang, R; Yu, D; Li, Z
Abstract : Background: mTOR signaling is proved to be one of the most important pathway in the pathogenesis in SLE. However, in patients with SLE, whether mTOR pathway can be activated by low-dose IL-2 remained unclear. Objectives: To clarify the effects of low-dose IL-2 therapy on mTOR signaling in the treatment of SLE. Methods: Eight patients with active SLE were treated with 1 million IU IL-2. Phophrylation of S6 ribosomal protein (S6RP), AKT and pSTAT5 were measured before and after the first 2 week of low-dose rhIL-2 administration. C57BL/6 mice (male, 8–12 weeks old) were intraperitoneally immunized with SRB and followed by administration of different doses (low:10, 000 IU and hight:300, 000 IU) of rhIL-2 or PBS from day 3 to day 9. The ratio of Th1, Th2, Tfh, Th17, Tfh and Treg as well as the level of S6RP, AKT and pSTAT5 were assayed by flow cytometry Results: Low-dose IL-2 was efficient and well tolerated in active SLE, and was associated with expansion of Treg cells (p<0.001) and reductions of Tfh and Th17 cells (p≤0.001). No significant change of pS6RP and pAKT was observed. On the other hand, there was a signfciant induction of the activation of STAT5. In mouse studies, low-dose IL-2 inhibited the differentiation of Th17 cells and Tfh cells. Comparing with high dose IL-2 group, there was no significantly increased mTOR activity after low-dose IL-2 administration. Conclusions: Low-dose IL-2 might circumvent mTOR pathway and play a regulatory role in the T cells in lupus Disclosure of Interest: None declared